2021
DOI: 10.20944/preprints202104.0383.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Future of Construction Industry: COVID-19 and Its Implications on Construction Projects and Risk Management – A Review

Abstract: The global coronavirus (COVID-19) pandemic has created a whole new set of risks in construction industries generating unprecedented delays, disruptions, and uncertainty on construction projects, and has forced the industries in adopting more sophisticated technologies while combating the reduced workforce on job sites. Further, the post-pandemic era of construction is expected to be a lot different as the industries will embrace the technology as the augmentation and collaboration strategy. Thus, it will be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 7 publications
(6 reference statements)
0
28
0
Order By: Relevance
“…In addition, the operation of small and medium-sized construction companies was supported financially. In addition to these measures, several previous studies have suggested establishing a disaster response system, revitalizing production methods and technology development, and establishing new safety practices as mid-to long-term measures for the construction industry in response to COVID-19 [3,4,[11][12][13][14].…”
Section: Recovery After Covid-19mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the operation of small and medium-sized construction companies was supported financially. In addition to these measures, several previous studies have suggested establishing a disaster response system, revitalizing production methods and technology development, and establishing new safety practices as mid-to long-term measures for the construction industry in response to COVID-19 [3,4,[11][12][13][14].…”
Section: Recovery After Covid-19mentioning
confidence: 99%
“…Studies that have addressed recovery after COVID-19 have primarily focused on emergency support for construction sites, measures to return construction companies to a standard operating environment, and mid-to long-term measures for the construction industry [3,4,[11][12][13][14]. Specific measures for emergency support for construction sites have included early payment for public projects, expansion of the scope of use of occupational safety and health management expenses, improvement of regulations associated with the extension of the contract period and adjustments, temporary relief for working hours, and administrative support for material procurement and labor supply.…”
Section: Key Initiatives For the Transformation Of The Construction I...mentioning
confidence: 99%
See 2 more Smart Citations
“…261-284) -one of them is also the construction sector. As declared by Adhikari and Poudyal (2021), the economic consequences of the pandemic have created a new set of risks in this sector of the economy related to disruptions, delays, or uncertainty in construction projects. The situation in the construction sector is worsened by disorder in supply chains and financial bubbles, which can lead to another recession.…”
Section: Introductionmentioning
confidence: 99%